Formação acadêmico-profissional de professores Surdos: barreiras e estratégias de apoio no curso DUA na prática - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The discussion on academic-professional training of Deaf teachers is a relevant topic for the implementation of training strategies that enable the construction of significant knowledge by the participating subjects. In this context, this research presents the results obtained through a case study, with a qualitative, exploratory approach, which investigated the academic-professional training of Deaf teachers, within the scope of the DUA in practice improvement course, offered to Basic Education teachers in Brazilian public schools. As a research field, the DUA in practice improvement course is presented, which had 27 classes, and among these 27 classes, there is a bilingual Collaboration class. The course was proposed as one of the actions of the Inclusive Pedagogical Gatherings of Pampa Extension Program developed by the Federal University of Pampa. In this context, the following research question was defined: how does the DUA in practice course guarantee accessibility to Deaf teachers who participate in the training? The subjects investigated were the nine Deaf students in the Collaboration class and the two translators/interpreters of the course. Two distinct semi structured interviews were used as research instruments, one of which was applied to the Deaf students and the other to the translators/interpreters of Libras. A documentary analysis of the Institutional Project of the Extension Program Inclusive Pedagogical Gatherings of Pampa was also carried out, as well as the course plan, training notebooks and videos of the gatherings held during the DUA in practice course. Data analysis was based on content analysis (Bardin, 1977), based on three defined categories: 1. Academic-professional training of teachers from an inclusive perspective with a focus on accessibility; 2. Barriers and support for the training of Deaf teachers considering multiple forms of teaching and learning; and 3. Professional practice based on the contributions of training, considering collaborative work. In this sense, when analyzing the DUA course in practice, the academic-professional training regarding accessibility was verified, the barriers faced by Deaf teachers were mapped, and the strategies and support made available to ensure accessibility were identified. Thus, the various accessibility strategies implemented to remove barriers were listed, such as: participation of Libras translators/interpreters, use of subtitles, insertion of visual resources in theoretical materials and live sessions, interaction via chat, organization of a bilingual class, and the development of collaborative work to read theoretical materials, based on sight translation (Sampaio, 2022). It was concluded that the DUA improvement course in practice offered academic-professional training from an inclusive perspective, based on the premise of identifying and removing barriers, thus ensuring the necessary accessibility for the participation and learning of Deaf students, through different strategies implemented. Furthermore, the positioning of the teacher trainers aligned with the theory, allowed the students to follow the implementation of accessibility strategies in practice, so that the collaborative nature of the training was fundamental for reflections and construction of knowledge.
Keywords: Formação acadêmico-profissional; Educação de surdos; Barreiras; Inclusão; Academic-professional training; Education of the deaf; Barriers; Inclusion; CNPQ::CIENCIAS SOCIAIS APLICADAS